(untitled) (Veterinária Notícias, 2022)
The relationship between man and animal has narrowed over the years, causing them to be considered as family members. However, not all tutors are aware of the correct ways of raising animals, so the study of population knowledge about the management and breeding of dogs and cats is of paramount importance for improving animal health and welfare. The objective was to evaluate the population’s level of knowledge about the ways of handling and breeding dogs and cats. The present work consists of the application of an online questionnaire to the population of Patrocínio-MG. The questionnaire included objective questions about the tutor’s personal data, animal data, forms of care, management and prevention of diseases. The percentage values ​​obtained in each question were compared by the x2 test at 5% of significance. A total of 398 people were interviewed, 53 of which were removed for not having animals, or for raising animals other than dogs and cats. Most of the interviewees are up to 25 years old, have secondary education and have a salary range of one minimum wage. This population has a greater preference for breeding dogs, with defined breeds, adults, with dry food being the food preferably supplied to the animals. The tutors carry out antiviral and rabies vaccination in animals from puppies with a booster dose annually, with deworming carried out periodically. It is concluded with the present work that the population has knowledge about the forms of care and management of dogs and cats, performing basic care in them.